Avalanche Multiplication and Noise Characteristics of Thin InP p+–i–n+Diodes - You, Ah Heng; Ong, Duu Sheng (2004)
A simple random path length model for computing the statistics of avalanche gain and excess noise factor in thin InP p(+)-i-n(+) diodes is presented. We incorporate the dead-space effect in our model, which is expected to play an important role in reducing noise in homejunction InP avalanche photodiodes (APDs). It is shown that the dead-space effect reduces avalanche noise when the device length is small. Our model is able to simulate the characteristics of multiplication gain and noise including the dead-space effect in InP p+-i-n+ diodes, particularly at device lengths omega of 0.1 mum and 0.2 mum. We demonstrated that the dead-space effect and feedback impact ionization are the dominant effects for improving excess noise factor in thin InP APDs.